PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MANAJEMEN MUTU PENDIDIKAN DI MADRASAH IBTIDAIYAH - Muflihah, Anik; Haqiqi, Arghob Khofya (Pascasarjana IAIN Kudus, 2019)
This study aims to study and describe the role of school principals in improving education management in MI NU Raudlatut Tholibin Japanpakis Jati Kudus. The research method used in this study is descriptive qualitative research using observation techniques and also interviews with the principal of the research location. The results obtained explained that the principal had made various efforts and had improved to support the management of education in MI NU Raudlatut Tholibin. Efforts made related to the important role in terms of leadership and management of madrasas both for teachers, students, facilities and other school supporters. The conclusion in this study is that the role of the principal is very important in improving education management and the role of the principal must be carried out in the role of educators, managers, administrators, supervisors, leaders, innovators and motivators.